2018
DOI: 10.7759/cureus.3230
|View full text |Cite
|
Sign up to set email alerts
|

American Heart Association High Blood Pressure Protocol 2017: A Literature Review

Abstract: Hypertension is the most prevalent clinical symptom arising from various cardiovascular disorders. Likewise, it is considered a precursor or sequelae to the development of acute coronary artery disease and congestive heath failure (CHF). Hypertension has been considered a cardinal criterion to determine cardiovascular function. According to the World Health Organization (WHO) global observatory data, hypertension causes more than 7.5 million deaths a year, about 12.8% of the total human mortality. Similarly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…As reported by the World Health Organization (WHO), coronary heart disease (CHD) is a primary cause of both men and women's mortality, which results in more than 7 million deaths annually [1]. It is widely accepted that type 2 diabetes mellitus (T2DM) is also one of the important risk factors for CHD.…”
Section: Introductionmentioning
confidence: 99%
“…As reported by the World Health Organization (WHO), coronary heart disease (CHD) is a primary cause of both men and women's mortality, which results in more than 7 million deaths annually [1]. It is widely accepted that type 2 diabetes mellitus (T2DM) is also one of the important risk factors for CHD.…”
Section: Introductionmentioning
confidence: 99%
“… 5 According to the World Health Organization (WHO), CHD is the leading cause of death for both men and women with more than 7 million deaths per year. 7 Related studies have also shown that CHD is one of the most common causes of the death of T2DM, and CHD accounts for approximately 65% of the deaths of diabetic patients. 8 T2DM is one of the important risk factors for CHD, and the risk of CHD in diabetic patients is twice that in nondiabetic patients.…”
Section: Introductionmentioning
confidence: 98%
“…1,2 This disease cause continuous end-organ damage leading to chronic kidney disease, ischemic heart disease, retinopathies and increased risk for stroke. 3 Primary prevention has been the main aim for reducing the overall disability. However, it is usually not achievable, so management lies in pharmacological agents and non-pharmacological methods, depending upon the choice and resources of the patient and the available expertise.…”
Section: Introductionmentioning
confidence: 99%